Riccardia verticillata Gradst. & Reeb, a new dendroid species of Riccardia (Aneuraceae) from the Cordillera del Cóndor, Ecuador. (2nd October 2019) - Gradstein, S. Robbert; Reeb, Catherine; Persson, Claes; Zapata, Nicolás; Pérez, Álvaro J.
Abstract : Introduction . The Cordillera del Cóndor on the border between Ecuador and Peru stands out because of its rich biodiversity and high endemism. Here we describe a new dendroid species of the thalloid liverwort genus Riccardia, R. verticillata Gradst. & Reeb, from El Quimi Biological Reserve in the Cóndor region of Ecuador. Methods . The plants are described using anatomical and morphological methods. For the anatomical study, plants were treated with bleach (20%) and stained with methylene blue, enhancing observation of the thallus structure. Key results. The plants consist of a stout, erect axis with a subepidermis and regularly spaced, horizontally spreading and flattened, densely 4–6 pinnate fronds, which are arranged in whorls. The axis and primary branches are wingless; the younger branches are broadly winged. An erect axis with a subepidermis and winged branches are also seen in the neotropical R. aberrans, R. ciliolata, R. fucoidea, R. gradsteinii, R. pallida, R. poeppigiana and R. wallisii, but these species are less densely pinnate and the branches are not arranged in horizontally spreading, flattened whorls, and are mostly fully winged. In its verticillate habit, the new species is similar only to members of R. subg. Arconeura, including R. prehensilis from Tierra del Fuego and R. eriocaula from Australasia. A key to dendroid neotropical species of Riccardia is provided. Conclusion . Riccardia verticillata stands out among neotropical Riccardia species by its markedly whorled habit. This discovery adds a further endemic taxon to the Cóndor region.